Interpreting the Parables - Blomberg, Craig L., 1955- (Downers Grove, IL: IVP Academic, 2012)
In the last century, more studies of the Parables were produced than for any other section of comparable length in the Bible, the problem is that most Bible readers are likely ever to know of most of them in this substantially new and expanded edition, Crig Blomberg surveys and evaluates contemporary critical approaches to the parables, challenging the prevailing consensus and making his own important new contribution to Parable studies. Witihin proper definitions and boundaries, the author defends a limited allegorical approach in support of this view of parable interpretation, Blomberg not only sets froth theatrical considerations but devotes attention to all the major parables, providing brief interpretations that high light the insights to be gained from his distinctive method: interpreting the parables can be read with profit by scholars, students pastors and educated lay people.--Publisher.
Includes bibliographical references and indexes
Keywords: Jesus Christ -- Parables